2017
DOI: 10.1073/pnas.1700092114
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobicity of proteins and nanostructured solutes is governed by topographical and chemical context

Abstract: Hydrophobic interactions drive many important biomolecular selfassembly phenomena. However, characterizing hydrophobicity at the nanoscale has remained a challenge due to its nontrivial dependence on the chemistry and topography of biomolecular surfaces. Here we use molecular simulations coupled with enhanced sampling methods to systematically displace water molecules from the hydration shells of nanostructured solutes and calculate the free energetics of interfacial water density fluctuations, which quantify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
135
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(151 citation statements)
references
References 66 publications
16
135
0
Order By: Relevance
“…Our findings are consistent with those of Pettitt and co-workers, who showed that the conformation of alkane chains and peptides can influence their hydration free energies substantially [66][67][68]. Our results also lend further support to the notion that surface-area models, which are commonly used to estimate the driving force of hydrophobic assembly, but are incapable of capturing subtle but important differences between the rigid and flexible solutes, are not appropriate for a quantitative treatment of hydrophobic hydration and interactions [66,69].…”
Section: B Hard-sphere Alkanesupporting
confidence: 91%
“…Our findings are consistent with those of Pettitt and co-workers, who showed that the conformation of alkane chains and peptides can influence their hydration free energies substantially [66][67][68]. Our results also lend further support to the notion that surface-area models, which are commonly used to estimate the driving force of hydrophobic assembly, but are incapable of capturing subtle but important differences between the rigid and flexible solutes, are not appropriate for a quantitative treatment of hydrophobic hydration and interactions [66,69].…”
Section: B Hard-sphere Alkanesupporting
confidence: 91%
“…19,22,[26][27][28][29][30][31][32][33][34][35] In contrast with simple hydrophobic or hydrophilic surfaces, proteins display nanoscopic chemical and topographical patterns, which influence their interactions with water in nontrivial ways. 20,[36][37][38][39][40][41][42][43][44][45][46] By interrogating how protein hydration waters respond to an unfavorable potential, here we find that the hydration shells of diverse proteins are also situated at the edge of a dewetting transition. Such a resemblance of protein hydration shells to extended hydrophobic surfaces appears to arise from the fact that -even for protein surfaces that are enriched in polar and charged residues -roughly half the surface consists of hydrophobic atoms.…”
Section: Introductionmentioning
confidence: 78%
“…[11][12][13] Common implicit solvation models describe water-mediated interactions based on a context-independent classification of molecular surfaces as either hydrophobic or hydrophilic. While such approaches provide qualitative insights, experiments 14 and explicit solvent simulations [15][16][17] show that the atomistic detail of molecular surfaces significantly affects interactions with an aqueous solvent. This is particularly the case in the context of chemically and topologically heterogeneous surfaces of biomolecules, where microscopic features ultimately determine whether solvent/water-mediated interactions between two interfaces are attractive or repulsive.…”
Section: Introductionmentioning
confidence: 99%
“…Useful insights into local hydrophobic or hydrophilic properties of a molecular surface can be obtained from local water density fluctuations that are easily analyzed in explicit solvent computer simulations. [15][16][17][18] The latter are increased in the case of hydrophobic surfaces, while attractive interactions of water with a polar surface suppress fluctuations. 15 As an alternative to the analysis of density fluctuations, explicit solvent simulations in the presence of small hydrophobic probe particles show directly where attractive water-mediated interactions result in an increase in the local concentration of the probe particles.…”
Section: Introductionmentioning
confidence: 99%